Jahresbericht 2020 der Universitätsbibliotheken der TU Berlin und UdK Berlin - Christof, Jürgen; Zeyns, Andrea (Wissen im Zentrum : Rechenschaftsbericht / Universitätsbibliothek, Technische Universität Berlin, 2021)
In their sixth joint Annual Report, the University Libraries of Technische Universität Berlin (TU Berlin) and Berlin University of the Arts (UdK Berlin) report on a year that was extraordinary in every respect. The coronavirus pandemic disrupted all plans and presented all staff with unforeseen challenges and difficulties. However, the year also brought forth much positive change. Staff report about developments in library use, media processing, IT services, digital teaching, science communication, and vocational training. An illustrated calendar lists important events from 2020. The 2020 Annual Report is concluded with an overview of selected key figures, information about the subject librarians, and a list of publications by library staff.